Evaluation of yam varietal response to vine multiplication technique under three growth media. - Agbesi, Shine (2017)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology (KNUST), Kumasi, in partial fulfillment of the requirement for the award of MPhil. Agronomy degree.